Integrating digital marketing for enhanced banking performance - Mohamad, Balouza (Edelweiss Applied Science and Technology, 2024)
This study aims to explore the correlation between digital marketing and banking performance in terms of customer relationships, innovation, retention, and financial perspectives. It assesses how the use of the digital elements should go beyond has more than the traditional marketing techniques to change to suit the customer expectation and embracing of technologies. The first research question raises a question with regard to how digital marketing affects/benefits the bank and how it complements conventional marketing. In light of that, the study seeks to holistically measure the effects of digital marketing on banking performance, analyze interactions of digital and conventional promotional strategies, compare customer acquisition/retention output, and review financial consequences of embracing digital procedures. Hypotheses are developed around four key areas: The research measures customer relationships, service innovation, customer acquisition and retention, and financial performance. A sequential design is employed, prejudice to the fact that a combination of both quantitative data along with the qualitative analysis is utilized in an effort to offer a comprehensive perspective of the research question. This research work examines these impacts analyzing the case of Bank Audi – more specifically the Neobank project. The study establishes a close relationship between digital marketing and better relationship with customers as evident in the higher levels of engagement. Marketing communication comes out as the most innovative influencer dictating how new products and services are developed. Furthermore, marketing communications demonstrate their effectiveness in acquiring and maintaining customers and substantially increasing the revenues. Interviews with the Bank Audi’s executives reveal importance of digital marketing as the way to address clients’ expectations and improve organizational performance. The study further finds that for the banking sector to achieve the benefits of digitization, more investment is required in digital marketing technologies. This supports the need to carry out training and education on new trends in digital marketing and the need to incorporate improvement in data analytics in order to translate customer behaviors data into practical business strategies. This raises a question of how banks have to enhance the security of their data or how they can improve customer confidence as banking moves online.